Pendidikan Karakter Dalam Society 5.0: Transformasi Melalui Program Pancasakti Mathpreneur - Edy Santoso, Masfuad; Ekawati, Yulia Nur; Aprianto, Amarsyah; Ayu Fadhila, Salma; Widiastuti, Nining; Hesti, Siska; Anindita Purnomo, Elzha; Yuanita, Sindy; Dinda Hastinasyah, Putri; Hamdani, Agung; Ilfiana, Mila; Nurfitriyani, Devi; Wulandari, Siti; Marasakti, Puruhita; Nursyafitri, Febriani (Universitas Palangka Raya, 2024)
Era industrial revolution 4.0 requires someone to collaborate with information systems in all fields, especially education and entrepreneurship. However, a person's lack of soft skills, creativity and character can be an obstacle in solving all the challenges. So, there is need for programs such as the Pancasakti Mathpreneur Program to build character and entrepreneurial spirit in facing the era of industrial revolution 4.0 and being able to solve challenges in a technology-based society in the era of society 5.0. This program aims to build character in the era of society 5.0 through the Pancasakti Mathpreneur Program at the Tegal Muhammadiyah Orphanage and find out the role of orphanage children in building an entrepreneurial spirit. This activity involved 33 orphanage children and administrators. The service method using a qualitative approach. Data was taken using lecture, discussion, documentation and direct practice techniques. The results show that program has been implemented and has a positive impact in building the entrepreneurial spirit of orphaned children, such as increasing their sense of self-confidence, creativity and responsibility. Increasing independence and fostering entrepreneurial creativity thinking about what according consumer interests. Orphanage children can also managing a business which leads a leadership spirit. In the era of society 5.0, orphanage children are directed towards technology-based entrepreneurship as a means of innovating and marketing products/services.